2020
DOI: 10.1128/aem.00962-20
|View full text |Cite
|
Sign up to set email alerts
|

Strain Background, Species Frequency, and Environmental Conditions Are Important in Determining Pseudomonas aeruginosa and Staphylococcus aureus Population Dynamics and Species Coexistence

Abstract: Bacterial communities in the environment and in infections are typically diverse, yet we know little about the factors that determine interspecies interactions. Here, we apply concepts from ecological theory to understand how biotic and abiotic factors affect interaction patterns between the two opportunistic human pathogens Pseudomonas aeruginosa and Staphyloccocus aureus, which often co-occur in polymicrobial infections. Specifically, we conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 77 publications
3
23
0
Order By: Relevance
“…Our findings that ecological factors (well-mixed and static growth) affect P. aeruginosa antistaphylococcal activity and the outcome of P. aeruginosa - S. aureus coculture dynamics are fundamentally in agreement with recent work from Niggli and Kummerli ( 20 ), which showed that P. aeruginosa and S. aureus coexist in a laboratory medium that promotes aggregation by embedding in low levels of agar. However, that study did not observe an increase in P. aeruginosa relative fitness compared to S. aureus during growth in mixed conditions compared to agar conditions, which differs from our observations ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings that ecological factors (well-mixed and static growth) affect P. aeruginosa antistaphylococcal activity and the outcome of P. aeruginosa - S. aureus coculture dynamics are fundamentally in agreement with recent work from Niggli and Kummerli ( 20 ), which showed that P. aeruginosa and S. aureus coexist in a laboratory medium that promotes aggregation by embedding in low levels of agar. However, that study did not observe an increase in P. aeruginosa relative fitness compared to S. aureus during growth in mixed conditions compared to agar conditions, which differs from our observations ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…1A and B ). The reason for this is not clear, but it is likely explained by low aeration of the mixed culture condition used by Niggli and Kummerli ( 20 ). That study performed mixed coculture in laboratory medium in wells of 24-well plates, using a volume of 1.5 ml in a well with a maximum volume of 3.4 ml and shaking at 170 rpm ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations